The production and perception of English sibilant fricatives by Mandarin speakers / Seyed Sepehr Sadrieh - Sadrieh, Seyed Sepehr (2014)
The use of English language is mostly restricted to classrooms in China and many Chinese learners have difficulties in the actual use of the language with one of the prominent areas of difficulty being pronunciation. Although there have been previous studies in the area of pronunciation difficulty faced by Chinese learners of English whose first language is Mandarin, there is a lack of research on a common area of difficulty for such speakers when it comes to the pronunciation of English: fricatives in general and English sibilant fricatives in particular. This study attempts to fill this gap through two main tasks in order to investigate and compare the production and perception of English sibilant fricatives by eight male and eight female native Mandarin speaking college students from China. In the production task, the participants were recorded reading a list of 31 English words with the four sibilants in different word positions. Five native speakers of standard American English then rated the sibilants produced by the participants in relation to the degree of ‘nativeness’ of their pronunciation. The results indicate that the participants had the most difficulty with /ʒ/ followed by /z/, /ʃ/ and /s/. In the perception test, the same Chinese participants listened to and selected the odd item in each instance of the perception task. The results indicate that the participants had the most difficulty distinguishing English /s/ from Mandarin /s/. However, they correctly picked most of the odd items out in words containing the rest of the sibilants. This suggests that the participants’ perception of English sibilant fricatives was generally better than their production of the same sounds except for /s/. This can be attributed to the fact that the difference between English and Mandarin /s/ is only phonetic and hard to detect for both English and Mandarin L1 speakers. Based on Flege’s Speech Learning Model (1995), this could be the result of filtering out of L2 sound features through Ll phonology due to the fact that these features are phonetically important but not phonologically so. The findings of this study help us understand the ` iii nature of Chinese language leaners’ production and perception of English sibilant fricatives and also contribute to the growing body of research on the production and perception of these sibilants in different varieties of English.